Arabic Translation Works in Expressing a Resistance: Case Study in Colonized Land Poetry of Nizar Qabbani - Muhammad Yunus Anis; Ali Mohammed Saleh Al-Hamzi (Institut Agama Islam Negeri (IAIN) Kendari, 2023)
This research examined the poetry written by Nizar Qabbani in Arabic, which has been translated into Bahasa Indonesia. The investigation was related to how the expression of resistance from the source language into the target language can be used as one of the main media against a regime. This study used a qualitative approach. The data in this study are language units in the form of phrases, clauses, and sentences, in the source language (Arabic) and the target language (Bahasa Indonesia). Data analysis used the Spradley model, namely domain analysis, taxonomic analysis, componential analysis, and cultural analysis to find the relationship and meaning between the expression of resistance in poetry and aspects of micro and macro translation. The findings attempted to map what translation techniques appear in the expression of resistance in political poetry and how the tendencies of these techniques are at a macro level, whether the translation technique is more oriented towards the source language or the target language. The contribution of the research theoretically tries to show that literary works are an effective and elegant medium in conveying criticism of the government. The study of translation techniques should consider a particular literary genre, as literary genres influence the use and selection of translation techniques.